Infectious Disease Control and Management in Ethiopia: A Case Study of Cholera - Park, Se Eun; Jeon, Yeonji; Kang, Sunjoo; Gedefaw, Abel; Hailu, Dejene; Yeshitela, Biruk; Edosa, Moti; Getaneh, Mesfin Wossen; Teferi, Mekonnen (Frontiers in Public Health, 2022)
Cholera remains a significant public health problem among the vulnerable populations living in many resource-limited settings with poor access to safe and clean water and hygiene practice. Around 2.86 million cholera cases and 95,000 deaths are estimated to occur in endemic countries. In Ethiopia, cholera has been one of the major epidemic diseases since 1634 when the first cholera outbreak was recorded in-country. Several cholera epidemics occurred with recent outbreaks in 2019-2021. Cholera has been often reported as acute watery diarrhea due to limited diagnostic capacity in remote areas in Ethiopia and sensitivities around cholera outbreaks. The government of Ethiopia has been executing several phases of multi-year health sector development plan in the past decades and has recently developed a national cholera control plan. Here, we aim to present the existing cholera control guidelines and health system in Ethiopia, including case detection and reporting, outbreak declaration, case management, and transmission control. Challenges and way forward on further research and public health interventions are also discussed to address the knowledge and health service gaps related to cholera control in Ethiopia.